Peningkatan Literasi Polis Standar Kendaraan Bermotor Indonesia Pada Warga DKI Jakarta - Dewanto, Dedy; Rozamuri, Arif Murti; Nurhadi, Elan; Basid, Rezqi Ananda; Mauludianna, Sri Morisonya; Susanto, Erwin; Sofia, Evi; Kusumawati, Fiska; Arham, Muhammad; Pranyoto, Suhari (Jurnal Abdimas Dedikasi Kesatuan, 2025)
One of the tasks of community service is to increase the Literacy of Motor Vehicle Insurance Policy to the Residents of DKI Jakarta, where the policy holders certainly want excellent service both in acceptance and claims. This community service activity is based on Increasing Literacy of Motor Vehicle Insurance Policy to the Residents of DKI Jakarta in order to Increase Awareness, Duty Utmost Good Faith, Excellent Service to Insurance Policy Holders. Motor Vehicle Insurance Policy holders face great challenges when driving in DKI Jakarta and its surrounding areas which are often congested and dense. So the potential for friction, collisions, and traffic accidents is quite high. Until 2023 the number of two-wheeled motorized vehicles in DKI Jakarta is 18.22 million units, while the number of four-wheeled motorized vehicles is 3.83 million units. (BPS DKI Jakarta, 2024). Therefore, it is very important for policyholders to know the terms and conditions of the policy, their rights and obligations at the time of closing and when a claim occurs due to friction, collision or traffic accident. So Increasing Literacy of Insurance Policy to the Residents of DKI Jakarta is appropriate, because Residents who own motorized vehicles are the driving force of company/institution operations where security and protection guarantees for their vehicles are very important. The implementation method was carried out by inviting approximately 200 DKI Jakarta residents who own policies/motor vehicle owners to a community service event at the Pertamina University Auditorium, where the resource person delivered material explaining the understanding of the policy contents. Next, a question and answer session, a quiz with prizes, and participant feedback were conducted, which resulted in a lot of enthusiasm among the audience. The conclusion is that the method for increasing motor vehicle policy literacy can be done through socialization/counseling together with a fairly high frequency.   Keywords : policy literacy, policy holder, Motor Vehicle (KBM) policy